Post-traumatic stress disorder: the role of the amygdala and potential therapeutic interventions – a review - Davis, Lori L.; Hamner, Mark B. (Frontiers in Psychiatry, 2024)
Introduction: Post-traumatic stress disorder (PTSD) is a psychiatric disorder triggered by exposure to a life-threatening or sexually violent traumatic event, and is characterized by symptoms involving intrusive re-experiencing, persistent avoidance of associated stimuli, emotional and cognitive disturbances, and hyperarousal for long periods after the trauma has occurred. These debilitating symptoms induce occupational and social impairments that contribute to a significant clinical burden for PTSD patients, and substantial socioeconomic costs, reaching approximately $20,000 dollars per individual with PTSD each year in the US. Despite increased translational research focus in the field of PTSD, the development of novel, effective pharmacotherapies for its treatment remains an important unmet clinical need. Observations: In this review, we summarize the evidence implicating dysfunctional activity of the amygdala in the pathophysiology of PTSD. We identify the transient receptor potential canonical (TRPC) ion channels as promising drug targets given their distribution in the amygdala, and evidence from animal studies demonstrating their role in fear response modulation. We discuss the evidence-based pharmacotherapy and psychotherapy treatment approaches for PTSD. Discussion: In view of the prevalence and economic burden associated with PTSD, further investigation is warranted into novel treatment approaches based on our knowledge of the involvement of brain circuitry and the role of the amygdala in PTSD, as well as the potential added value of combined pharmacotherapy and psychotherapy to better manage PTSD symptoms.